Distribution and ecological habitat of Scenedesmus and related genera in some freshwater resources of Northern and North-Eastern Thailand - KITTIYA PHINYO; JEERAPORN PEKKOH; YUWADEE PEERAPORNPISAL (Society for Indonesian Biodiversity, 2017)
Phinyo K, Pekkoh J, Peerapornpisal Y. 2017. Distribution and ecological habitat of Scenedesmus and related genera in some freshwater resources of Northern and North-Eastern Thailand. Biodiversitas 18: 1092-1099. The family Scenedesmaceae is made up of freshwater green microalgae that are commonly found in bodies of freshwater, particularly in water of moderate to polluted water quality. However, as of yet, there have not been any studies on the diversity of this family in Thailand and in similar regions of tropical areas. Therefore, this research study aims to investigate the richness, distribution and ecological conditions of the species of the Scenedesmus and related genera through the assessment of water quality. The assessment of water quality was based on the physical and chemical parameters at 50 sampling sites. A total of 35 taxa were identified that were composed of six genera, i.e. Acutodesmus, Comasiella, Desmodesmus, Pectinodesmus, Scenedesmus and Verrucodesmus. Eleven taxa were newly recorded in Thailand. The taxa were found in the oligo-mesotrophic to the eutrophic status. The major study sites were influenced by the nutrients identified in the water resources. The dominant species were Desmodesmus communis (E. Hegewald) E. Hegewald, D. armatus var. bicaudatus (Guglielmetti) E. Hegewald, D. armatus (Chodat) E. Hegewald and D. serratus (Corda) S. S. An, Friedl & E. Hegewald. This study has produced revised material on Scenedesmus and related genera in Thailand that is considered important information with regard to the classification of microalgae in Thailand.